Exploring heritage & art at Galeri Diraja Arau: reflections from an academic visit / Azlan Salim … [et al.] - Salim, Azlan; Mohamad Saber, Joesri; Zaeimoedin, Teku Zariff; Mat Noor, Syuhirdy (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
On 26th June, 2024, faculty members from the Faculty of Hotel and Tourism Management, UiTM Penang visited Galeri Di Raja Arau in Arau, Perlis. This visit provided an opportunity to delve into the gallery's role in preserving and showcasing the cultural heritage of the Perlis royal family. While the specifics of our Visit are secondary, understanding the gallery's significance offers valuable insights into its broader educational and cultural impact.